1997
DOI: 10.1177/108835769701200102
|View full text |Cite
|
Sign up to set email alerts
|

Employer Attitudes and Satisfaction with Supported Employment

Abstract: The attitudes of employers toward workers with severe mental and physical disabilities and supported employment programs were examined through structured interviews with 47 employers who had hired or supervised workers participating in supported employment programs in Tennessee. Results indicated that employers generally hold favorable attitudes regarding the employment potential of workers with disabilities and the quality of services provided through supported employment programs. The physical presence of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…Nevertheless, for employees with disabilities, educators ranked "ability to seek for help" higher than most other skills, whereas employers rated "ability to show high regard for safety procedure" as one of the top five important skills. Consistent with a number of previous studies, "safety" was one of the major concerns of the employers when hiring employees with disabilities (Blanck, 1998;Petty & Fussell, 1997). Although not warranted, this concern may potentially cause employer bias toward not hiring individuals with disabilities, or even workplace discrimination.…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, for employees with disabilities, educators ranked "ability to seek for help" higher than most other skills, whereas employers rated "ability to show high regard for safety procedure" as one of the top five important skills. Consistent with a number of previous studies, "safety" was one of the major concerns of the employers when hiring employees with disabilities (Blanck, 1998;Petty & Fussell, 1997). Although not warranted, this concern may potentially cause employer bias toward not hiring individuals with disabilities, or even workplace discrimination.…”
Section: Discussionsupporting
confidence: 60%
“…Researchers have studied employers' perceptions of persons with disabilities predominantly by surveying employer representatives who have the responsibility of hiring or supervising (e.g, Diksa & Rogers, 1996;Ehrhart, 1994;Johnson et al, 1988;Levy et al, 1993;Marcouiller et al, 1987). Samples have also consisted of employers drawn from local (e.g., Gruenhagen, 1982;Kregel & Unger, 1993;Phillips, 1975;Thakker, 1997) and regional geographical areas (e.g., Blanck, 1998;Levy et al, 1993;Petty & Fussell, 1997) as well as nationally (e.g., Ehrhart;Levy et al, 1992;McFarlin et al, 1991). Methods for collecting data have included mail surveys (e.g., Fuqua et al, 1984;Gade & Toutges, 1983), where findings often revealed low return rates in comparison to research utilizing telephone (e.g., Diksa & Rogers, 1996) or face-to-face interviews (e.g., Johnson et al, 1988;Kregel & Unger, 1993), which often reported higher participation rates.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 24 studies reviewed, only 7 involved samples composed of predominantly supervisors or managers with direct experience with a worker with a disability (e.g., Blanck, 1998;Du Pont, 1993;Kregel & Unger, 1993;Petty & Fussell, 1997;PittCatsouphes & Butterworth, 1995;Shafer et al, 1987;Shafer et al, 1988). Results from studies that have surveyed directline managers or supervisors indicated that they were generally satisfied with the work performance of employees with disabilities (Blanck; Du Pont; PittCatsouphes & Butterworth; Shafer et al, 1987).…”
Section: Type Of Researchmentioning
confidence: 99%
“…Nine studies conducted since 1987 all have reported positive attitudes on the parts of employers toward employees with disabilities that came from vocational rehabilitation or supported-employment programs (Cooke, Pickett-Schenk, Banghart, Rosenheck, & Randolph, 2001;Coope, 1991;Eigenbrood & Retish, 1988;Kregel & Unger, 1993;Nietupski, Hamre-Nietupski, Vander-Hart, & Fishback, 1996;Petty & Fussell, 1997;Sandys, 1994;Shafer, Hill, Seyfarth, & Wehman, 1987;Wilgosh & Mueller, 1989). This trend could be indicative of employers having much more confidence in hiring PWDs who have institutional evidence of an education that would teach the required KSAOs.…”
Section: T a B L E I I Are Employer Concerns About Hiring People Withmentioning
confidence: 99%